2016
DOI: 10.2176/nmccrj.cr.2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenting in Right-sided Aortic Arch: A Case Report

Abstract: The present report describes a patient with pseudo-occlusion of the left internal carotid artery accompanied by aortic anomalies consisting of right-sided aortic arch with aberrant left subclavian artery arising from Kommerell’s diverticulum. Initial attempt of carotid artery stenting via the trans-femoral approach was unsuccessful because of low origin of the left common carotid artery. Therefore, carotid artery stenting (CAS) via the trans-brachial approach was successfully performed with distal balloon prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Patients with a right aortic arch with a left ligamentum arteriosum are more likely to develop Kommerell’s diverticulum, which is a remnant part of the left fourth aortic arch arising as a left SCA aneurysm. [ 14 ] An ALSA’s proximal segment that is conically dilated at its aortic origin is referred to as a diverticulum. However, it is also referred to as “lusoria root,” “remnant diverticulum,” and “lusoria diverticulum.” Kommerell’s diverticulum can be seen behind the trachea in 5% of cases, between the trachea and esophagus in 15% of cases, and in the retroesophageal region in 80% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with a right aortic arch with a left ligamentum arteriosum are more likely to develop Kommerell’s diverticulum, which is a remnant part of the left fourth aortic arch arising as a left SCA aneurysm. [ 14 ] An ALSA’s proximal segment that is conically dilated at its aortic origin is referred to as a diverticulum. However, it is also referred to as “lusoria root,” “remnant diverticulum,” and “lusoria diverticulum.” Kommerell’s diverticulum can be seen behind the trachea in 5% of cases, between the trachea and esophagus in 15% of cases, and in the retroesophageal region in 80% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] The other case was pseudo-occlusion of the left ICA. [ 14 ] We report a case of anterior circulation insufficiency due to symptomatic left CCA and ICA stenosis (30–50%) causing the patient’s symptoms. Furthermore, asymptomatic right CCA stenosis (30%) was traced only on the native brain CT scan as a watershed infarction of the left posterior, frontal, and parieto-occipital cortex but without any neurological deficit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpected anatomical variant of the aortic arch may increase procedural difficulty of neuro-EVT via the femoral artery approach. 8 Even in cases of patients with a normal aorta, the meandering of tortuous vessels tends to delay the femoral artery access procedure by 30 minutes or more, which is also associated with unsuccessful revascularization. 9 Neuro-EVT is often performed via femoral artery approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, if patients have not only mirror-image branching but some other anatomical variations, it may be difficult to advance guiding catheter into target vessels. Ohtani et al 6) reported a carotid artery stenting case for left internal carotid artery stenosis with right aortic arch. In that report, a 4 Fr modified Simmons catheter via trans-femoral approach could not be advanced into left common carotid artery because left common carotid artery was originated from the low part of ascending aorta.…”
Section: Discussionmentioning
confidence: 99%